Dispersion and stability of SiC ceramic slurry for stereolithography. Issue 4 (March 2020) - Ding, Guojiao; He, Rujie; Zhang, Keqiang; Xia, Min; Feng, Chengwei; Fang, Daining
Abstract: Stereolithography based additive manufacturing provides an effective method to fabricate complex-shaped SiC ceramic components. The dispersion and stability of the ceramic slurry are very important for stereolithography. In this study, the dispersion and stability of SiC ceramic slurries were investigated systematically. The effects of resin monomers, dispersants, particle size, solid loading and ball milling time on the dispersion, rheological behavior and stability of SiC ceramic slurries were studied in detail. Finally, an optimal SiC ceramic slurry for stereolithography based additive manufacturing was obtained, and complex-shaped SiC ceramic architectures were fabricated.